Catching "Montréal on the Move" and Challenging the Discourse of Unilingualism in Québec - Lamarre, Patricia (Anthropologica, 2013)
A complex linguistic dynamic is emerging in Mon tréal, yet most of the research on language in Québec relies on census statistics or survey data, leaving many questions unanswered. Specifically, what are young Montréalers who are increasingly bilingual and multilingual actually doing with languages as they move through the city and how do they per ceive traditional conceptions of language and identity? To an swer these questions, a non-static ethnographic approach was designed, following 15 multilinguals through their daily lives across sites and networks. Participants collaborated in analysis through discussion and reflection on the verbatim and texts col lected. The findings reveal a complex portrait of language in Montréal, challenging current ways of thinking about language and doing research.